L’école et les ambivalences du mérite - Duru-Bellat, Marie (2010)
While merit is a crucial basis to allocate individuals to unequal positions in modern societies, school is responsible for assessing it among pupils. Sociology of education shows that it is impossible, as long as societies are unequal, to consider that social inequalities in school attainment result from the diversity of pupils’ merit. In the same time, a perfect meritocracy would induce many negative consequences, both within school and in professional life. However, merit cannot be completely discarded, and this principle of justice should in fact be combined with other one such as need and equality. It remains that at the society level, the obsession of merit and the correlative promotion of equality of opportunity should not divert from fighting against inequalities themselves.